THE INFLUENCE OF HUMAN RESOURCE CAPACITY AND WORKLOAD ON EMPLOYEE PERFORMANCE IN SOUTH BURU REGENCY’S EMPOWERMENT AND PROTECTION AGENCIES - Rosmila Sela; Samson Laurens; Stanislaus Kostka Ohoiwutun (SOSIOEDUKASI, 2026)
This study examines the influence of human resource capacity and workload on employee performance in South Buru Regency’s empowerment and protection agencies. The research gap lies in the limited empirical studies that connect internal organizational factors with local public service challenges, particularly in community empowerment, village governance, women’s empowerment, and child protection services. Using a quantitative associative-causal design, data were collected from all 74 employees through total sampling and analyzed using multiple linear regression with SPSS. The results show that human resource capacity has a positive and significant effect on employee performance, indicating that knowledge, skills, experience, and competence improve task effectiveness. Workload also has a positive and significant effect, showing that proportionate task distribution can encourage productivity when aligned with employee capacity. Simultaneously, human resource capacity and workload significantly affect employee performance, with an R Square value of 0.774, meaning that 77.4% of performance variation is explained by both variables. The novelty of this study lies in its contextual analysis of employee performance in multi-functional local agencies facing social service pressures and child protection challenges. The findings imply that continuous training, certification, technical assistance, and balanced workload distribution are essential for improving public service quality.